2016
DOI: 10.1142/s0129055x16500124
|View full text |Cite
|
Sign up to set email alerts
|

Higher U(1)-gerbe connections in geometric prequantization

Abstract: We promote geometric prequantization to higher geometry (higher stacks), where a prequantization is given by a higher principal connection (a higher gerbe with connection). We show fairly generally how there is canonically a tower of higher gauge groupoids and Courant groupoids assigned to a higher prequantization, and establish the corresponding Atiyah sequence as an integrated Kostant-Souriau infinity-group extension of higher Hamiltonian symplectomorphisms by higher quantomorphisms. We also exhibit the infi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 81 publications
(198 reference statements)
2
43
0
Order By: Relevance
“…This is reflected in the fact that non‐homotopy theory has no answer to the evident followup question; if 2‐cocycles classify central extensions, then: “Whatdohighercocyclesclassify?”For example, the Lie algebra su(n) itself (for n2) carries no non‐trivial 2‐cocycle, but it carries, a non‐trivial 3‐cocycle (in fact precisely one, up to rescaling) given on elements x,y,zsu(n) by μ3(x,y,z)=true〈x,[y,z]false⟩0.16em,where [,] is the Lie bracket, and , the Killing form. This cocycle controls both the SU( n ) WZW‐model as well as SU( n )p‐Chern‐Simons theory (see [] for the higher‐structure perspective on this phenomenon) and hence is crucial both in field theory (gauge instantons) as well as in string theory (rational CFT compactifications).…”
Section: Higher Structure From Higher Cocyclesmentioning
confidence: 99%
“…This is reflected in the fact that non‐homotopy theory has no answer to the evident followup question; if 2‐cocycles classify central extensions, then: “Whatdohighercocyclesclassify?”For example, the Lie algebra su(n) itself (for n2) carries no non‐trivial 2‐cocycle, but it carries, a non‐trivial 3‐cocycle (in fact precisely one, up to rescaling) given on elements x,y,zsu(n) by μ3(x,y,z)=true〈x,[y,z]false⟩0.16em,where [,] is the Lie bracket, and , the Killing form. This cocycle controls both the SU( n ) WZW‐model as well as SU( n )p‐Chern‐Simons theory (see [] for the higher‐structure perspective on this phenomenon) and hence is crucial both in field theory (gauge instantons) as well as in string theory (rational CFT compactifications).…”
Section: Higher Structure From Higher Cocyclesmentioning
confidence: 99%
“…We prove that the topological charge structure of fundamental super M-branes produces twisted K-theory charges of Type IIA D-branes under double dimensional reduction when all torsion effects are ignored 1 . Our result is based upon Sati's conjecture [2] that the topological M-brane charge is classified by degree-4 cohomotopy, and our result in turn contributes to a growing body of evidence for this conjecture (see [3][4][5][6][7][8][9][10]).…”
mentioning
confidence: 64%
“…But in [21,22,39] we explained that the WZW-type sigma models for super p 2 -branes with (higher) gauge fields on the their worldvolume and on which super p 1 -branes may end, are globally defined not on target superspacetime X itself, but on the total space X of a super p 1 -stack extension X → X of superspacetime, which itself is a differential refinement of the p 1 -gerbeX that underlies the WZW term of the p 1 -branes. Moreover, in [16] we showed that the higher Heisenberg-Kostant-Souriau extensions of remark 2.11 generalizes to such higher stacky base spaces. Schematically this follows now by the following picture, the full details are in [38,39]: .…”
Section: Application To Brane Chargesmentioning
confidence: 75%
“…We indicate how the higher stacky Heisenberg-Kostant-Souriau extension of [16] generalizes this to higher gauged WZW models (such as the Green-Schwarz-type sigmamodel for the M5-brane) and produces cohomological corrections to the naive brane charges.…”
Section: Jhep03(2017)087mentioning
confidence: 80%
See 1 more Smart Citation